INVESTIGATION OF BULLYING IN HIGH SCHOOL STUDENTS BY GENDER AND SCHOOL TYPE - Rizvance Masan, Sehida (International Scientific Journal Vision, 2022)
The aim of this study is to examine the levels of peer bullying of high school students attending the 1st, 2nd, 3rd and 4th grades in terms of gender and type of school. The universe of the research consists of adolescents studying in the 1st, 2nd, 3rd and 4th grades of high schools in different cities of North Macedonia in the 2020-2021 academic year. The sample of the study consists of a total of 301 students, 215 girls and 86 boys, selected by simple random sampling method from each high school level in the cities of Skopje, Tetovo, Gostivar, Radoviş, Resne, Struga, Ohrid, Debre, Kırçova. The analysis of the data obtained in the study was carried out using the SPSS 22.0 package program. Pearson Correlation analysis, independent groups t-test, one-way analysis of variance (ANOVA) and Tukey Posthoc test were used in the analysis of the data in the study. .05 significance level was taken as basis in the statistics. As a result of the analysis of the research data; while it was seen that the peer bullying victimization subscale of high school students participating in the research differed significantly in terms of school type, no significant difference was found in the bullying and victimization subscales in terms of gender. The findings were discussed on the basis of the relevant literature and some suggestions were presented.